2012
DOI: 10.1002/tax.612004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in the species–rich Irano–Turanian genus Alcea (Malvaceae)

Abstract: The genus Alcea (Malvaceae) includes approximately 50 species of mainly Irano–Turanian distribution and is considered one of the most challenging genera of the Middle East, due to its uniformity and pronounced plasticity in morphological traits. Here, using three molecular markers (nrDNA ITS and the plastid spacers psbA–trnH and trnL–trnF), we present a phylogeny of Alcea and test previous infrageneric taxonomic hypotheses as well as its monophyly with respect to Althaea, a genus with which it has often been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…We analysed three molecular matrices: nrDNA (ITS), cpDNA (trnL-trnF, psbA-trnH, ndhF) and the cpDNA + nrDNA combined matrix (i.e., the concatenated dataset). The plastid genome behaves as a single linkage group (Escobar-García & al., 2012), so plastid markers were concatenated a priori using FASconCAT v.1.0 (Kuck & Meusemann, 2010). However, prior to concatenation of the cpDNA and nrDNA matrices, we checked the congruency between the nrDNA and cpDNA trees by visually inspecting incongruent placements of individual accessions or whole clades (Pirie, 2015) with Bayesian posterior probabilities ≥ 0.95 and bootstrap support > 70% (Hillis & Bull, 1993;Salichos & al., 2014); after removal of the incongruent accessions the cpDNA and nrDNA matrices were concatenated and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed three molecular matrices: nrDNA (ITS), cpDNA (trnL-trnF, psbA-trnH, ndhF) and the cpDNA + nrDNA combined matrix (i.e., the concatenated dataset). The plastid genome behaves as a single linkage group (Escobar-García & al., 2012), so plastid markers were concatenated a priori using FASconCAT v.1.0 (Kuck & Meusemann, 2010). However, prior to concatenation of the cpDNA and nrDNA matrices, we checked the congruency between the nrDNA and cpDNA trees by visually inspecting incongruent placements of individual accessions or whole clades (Pirie, 2015) with Bayesian posterior probabilities ≥ 0.95 and bootstrap support > 70% (Hillis & Bull, 1993;Salichos & al., 2014); after removal of the incongruent accessions the cpDNA and nrDNA matrices were concatenated and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…A handful of studies, all published in the last decade, have investigated the phylogenetic origins of individual IT elements [e.g. Cousinia (Asteraceae): López‐Vinyallonga et al, ; Isatis (Brassicaceae): Moazzeni et al, ; Scrophularia (Scrophulariceae): Attar et al, ; Delphinieae (Ranunculaceae): Jabbour & Renner, ; Haplophyllum (Rutaceae): Salvo et al, ; Alcea (Malvaceae): Escobar‐García et al, ; Limonium (Plumbaginaceae): Akhani et al, ; Centaurea (Asteraceae): Hilpold et al, ; Erysimum (Brassicaceae): Moazzeni et al, ; Eremurus , Asphodelus , and Asphodeline (Xanthorrhoeaceae): Naderi Safar et al, ; Acanthophyllum (Caryophyllaceae): Pirani et al, ]. Moreover, few studies have explicitly addressed the spatial and temporal relationships between the IT region and adjacent ones, such as the Saharo‐Arabian and Mediterranean regions [e.g.…”
Section: Evolutionary Perspectives On the Irano‐turanian Regionmentioning
confidence: 99%
“…For example, A. flavovirens and A. glabrata differ only in the size of the carpel and width of wing (PAKRAVAN, 2008). ESCOBAR et al (2012) with using three molecular markers (nrDNA ITS and the plastid spacers psbA-trnH and trnL-trnF), showed that a phylogeny of Alcea and test previous infrageneric taxonomic hypotheses as well as its monophyly with respect to Althaea, a genus with which it has often been merged. They additionally discuss morphological variation and the utility of morphological characters as predictors of phylogenetic relationships.…”
Section: Morphometric Analysesmentioning
confidence: 80%
“…From an industrial and medicinal point of view, Alcea is among the most important genera recognized in the family Malvaceae. Molecular-phylogenetic data also support the monophyly and distinctness (as suggested by morphological data) of Alcea but they are of limited use in determining relationships between species and species delimitations (ESCOBAR et al, 2012). Alcea exhibits a considerable taxonomic complexity (ZOHARY, 1963a,b;RIEDL, 1976;TOWNSEND, 1980).…”
Section: Introductionmentioning
confidence: 77%